Análise da virulência, sensibilidade antifúngica e mecanismos de resistência a azólicos em cepas de Candida tropicalis de origem humana e veterinária - Oliveira, Jonathas Sales de (2017)
Candida tropicalis, an yeast isolated as comensal from humans and other animals, is a major Candida species associated with serious invasive infections in humans, being also able to cause infection in several animal species. The present study aimed to analyze virulence factors, the susceptibility profile and mechanisms of resistance to azoles in human (n = 24) and veterinary (n = 28) isolates of C. tropicalis, as well as to evaluate the effect of promethazine on cells of C. tropicalis isolates resistant to azoles. In the first part of this research, the in vitro production of phospholipases and proteases, hemolytic activity, biofilm production and experimental infection using the nematode Caenorhabditis elegans was evaluated, as well as the susceptibility of planktonic and sessile cells against the antifungals fluconazole, itraconazole, voriconazole, caspofungin and amphotericin B. Total sterols content, efflux of rhodamine 6G and expression levels of CDR1, MDR1 and ERG11 genes in human (n = 13) and veterinary (n = 13) isolates were also assessed. Finally, the susceptibility of planktonic and sessile cells to promethazine alone and in combination with antifungals was analyzed using 2 strains resistant to azoles and a sensitive strain of C. tropicalis. Antifungal activity of promethazine was investigated through the time-kill curve and assessing the effects of the drug on the efflux of 6G rhodamine, cell size/granularity, membrane integrity and mitochondrial transmembrane potential, through flow cytometry. Regarding the in vitro production of virulence factors, 21.15% of the strains showed phospholipase production, 44.23% produced protease and 96% were positive for hemolytic activity. 98% of the strains were able to produce biofilm, most showing strong production (65.38%). High mortality rates of C. elegans were observed when worms were exposed to C. tropicalis strains, reaching 96% of death after 96 h of exposure to the strains. Concerning the antifungal susceptibility profile, 10 isolates were resistant to at least 1 azole and 5 isolates were resistant to all azoles tested. Caspofungin and amphotericin B showed the best inhibition results against C. tropicalis mature biofilm when compared to the azole antifungals. Paradoxical effect on mature biofilm was observed at high concentrations of caspofungin (8-64 μg/mL). Regarding the study of mechanisms of azole resistance, no difference was observed between total sterols contents of the groups analyzed, however, 6 fluconazole-non-susceptible isolates showed increased efflux of 6G rhodamine. Fluconazole-non-susceptible and fluconazole-less-susceptible isolates showed a mean expression for CDR1, MDR1 and ERG11 genes greater than the susceptible isolates, with 2 fluconazole-non-susceptible isolates showing high expression for all three genes. Promethazine showed inhibition of planktonic and sessile cells at concentrations of 64 and 128 μg/mL, respectively. The addition of sub-inhibitory concentrations of promethazine reduced the MIC of the azoles tested against the resistant strains, altering the resistance phenotype. Pre-incubation with promethazine reduced the efflux of 6G rhodamine, in addition to causing changes in cell size/granularity, plasma membrane damage and mitochondrial membrane depolarization. The present work showed that human and veterinary isolates of C. tropicalis presented similar production of virulence factors and pathogenicity. In addition, azole resistance in veterinary C. tropicalis strains is related, in part, to elevated ERG11 gene expression and efflux pump activity. Finally, promethazine shows synergism with azoles against resistant strains of C. tropicalis, causing cell membrane and mitochondrial activity impairment on fungal cells.